2015
DOI: 10.1186/s13567-015-0177-0
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of pigs with the S48 strain of Toxoplasma gondii – safer meat for human consumption

Abstract: As clinical toxoplasmosis is not considered a problem in pigs, the main reason to implement a control strategy against Toxoplasma gondii (T. gondii) in this species is to reduce the establishment of T. gondii tissue cysts in pork, consequently reducing the risk of the parasite entering the human food chain. Consumption of T. gondii tissue cysts from raw or undercooked meat is one of the main sources of human infection, with infected pork being considered a high risk. This study incorporates a mouse bioassay wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 41 publications
2
33
0
Order By: Relevance
“…All pigs in group 1, 2 and 3 were seropositive by ELISA by day 21 (for further details refer to (Burrells et al, 2015)). Mouse bioassay and MC-PCR results are presented in Table 13.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All pigs in group 1, 2 and 3 were seropositive by ELISA by day 21 (for further details refer to (Burrells et al, 2015)). Mouse bioassay and MC-PCR results are presented in Table 13.…”
Section: Resultsmentioning
confidence: 99%
“…(Full details of the results of the vaccination trial, including all tissues tested by mouse bioassay and ITS1 PCR can be obtained from the published manuscript (Burrells et al, 2015)). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A vaccine is available for sheep and goats that can prevent miscarriage owing to toxoplasmosis, says Elisabeth Innes, an immunologist at Moredun Research Institute near Edinburgh, UK, and one of the vaccine's developers. Her team has shown that the vaccine can also reduce the number of tissue cysts in food animals, potentially making the food supply safer 6 .…”
Section: Vaccine Vexationmentioning
confidence: 99%